Transient and Steady State Auditory Responses With Direct Acoustic Cochlear Stimulation. Issue 3 (May 2015) - Verhaert, Nicolas; Hofmann, Michael; Wouters, Jan
Abstract : Objectives: Direct acoustic cochlear implants directly stimulate the cochlear fluid of the inner ear by means of a stapes piston driven by an actuator and show encouraging speech understanding in noise results for patients with severe to profound mixed hearing loss. Auditory evoked potentials recorded in such patients would allow for the objective evaluation of the aided auditory pathway. The aim of this study was (1) to develop a stimulation setup for EEG recordings in subjects with direct acoustic cochlear implants, (2) to show the feasibility of recording auditory brainstem responses (ABRs) and auditory steady state responses (ASSRs), and (3) to analyze the relation between electrophysiological thresholds derived from these responses and behavioral thresholds. Design: For the three subjects implanted during a phase Ib clinical study in the authors' center, ABRs and 40 and 80 Hz ASSRs were recorded with a straightforward acoustic stimulation setup and a newly developed direct stimulation setup. Click trains with rates around 40 Hz and around 90 Hz were used as stimuli. By comparing amplitude growth function and phase delay in the same stimulus range, validity of the responses was confirmed. Results: With the acoustic stimulation setup, stimulation artifacts made it impossible to analyze responses. With the direct stimulation setup, stimulation artifacts could be removed completely and responses could be successfully recorded in a noninvasive manner in all subjects. Response properties such as ABR peak V latencies and ASSR apparent latencies were similar to those for acoustic stimulation, with apparent latencies of 39.9 and 24.7 msec for 40 and 90 Hz, respectively. Electrophysiological thresholds could be objectively determined from the ABRs and ASSRs. In the 40 Hz range, the mean difference between electrophysiological ASSR thresholds and behavioral ones was 12 dB. Conclusion: The results show that auditory evoked potential measurements with the developed direct stimulation setup are feasible and meaningful and should be further investigated to provide intraoperative feedback about the coupling of the actuator to the inner ear. Abstract : This study aims to develop a stimulation setup to record auditory evoked potentials (AEPs) in subjects with a direct acoustic cochlear stimulation system, enabling an objective evaluation of the aided auditory pathway. The evaluated device provides an encouraging hearing rehabilitation for the challenging treatment of severe to profound mixed hearing loss. With a direct stimulation setup, electrophysiological thresholds can be determined through the combined information of the amplitude response growth function and the phase delays of the responses. AEPs latencies are in line with electrophysiological auditory pathway studies.